A non-redundant role for Drosophila Mkk4 and hemipterous/Mkk7 in TAK1-mediated activation of JNK. - Geuking, P.; Narasimamurthy, R.; Lemaitre, B.; Basler, K.; Leulier, F. (PLoS ONE, 2009)
The JNK pathway is a mitogen-activated protein (MAP) kinase pathway involved in the regulation of numerous physiological processes during development and in response to environmental stress. JNK activity is controlled by two MAPK kinases (MAPKK), Mkk4 and Mkk7. Mkk7 plays a prominent role upon Tumor Necrosis Factor (TNF) stimulation. Eiger, the unique TNF-superfamily ligand in Drosophila, potently activates JNK signaling through the activation of the MAPKKK Tak1.In a dominant suppressor screen for new components of the Eiger/JNK-pathway in Drosophila, we have identified an allelic series of the Mkk4 gene. Our genetic and biochemical results demonstrate that Mkk4 is dispensable for normal development and host resistance to systemic bacterial infection but plays a non-redundant role as a MAPKK acting in parallel to Hemipterous/Mkk7 in dTAK1-mediated JNK activation upon Eiger and Imd pathway activation.In contrast to mammals, it seems that in Drosophila both MAPKKs, Hep/Mkk7 and Mkk4, are required to induce JNK upon TNF or pro-inflammatory stimulation.